Analysis of Factors Affecting Patient Satisfaction JKN Non PBI at Primary Health Care in East Jakarta District 2016 - Arbitera, Cahya; Sjaaf, Amal Chalik; Sulistiadi, Wahyu (Journal of Indonesian Health Policy and Administration, 2017)
Health development in the period 2015-2019 is Indonesia Sehat program with the goal to improve the health and nutritional status of the community through health and community empowerment efforts which are supported with financial protection and health care equity. Social Health Security Agency (BPJS) as JKN organizers estimate in 2015 is a deficit of more than 6 trillion rupiahs. In 2016, the deficit is estimated to be 11 trillion rupiahs. This study used a cross sectional study design. The population in this study were outpatients at the sub-district Kramat Jati and Pasar Rebo primary health care with the total number of 800 people and studied sample of 100 people. Patient satisfaction in this study has mean score of 43,06. Education variable; job and services are not significantly affects patient satisfaction JKN Non PBI at East Jakarta district primary heallth care. In conclusion, dimension of punctuality; convenience in obtaining services and ease in obtaining services most influence on patient satisfaction JKN Non PBI in East Jakarta district primary health care with the p value = 0,000 < 0,05. In addition, politeness and friendliness within the service still have big influence on patient satisfaction bicause it is important factors on patient satisfaction. Therefore, the author gives some recommendations to appropriate and thorough improvement added with upgrading to the punctuality of service, conducting a survey of patient satisfaction by BPJS and primary health care, disseminating the research results regarding the effect of service quality on patient satisfaction level, further and in-depth research needs to be done related to the effect on service quality dimension to JKN patient satisfaction level in all primary health care included in East Jakarta district, especially at primary health care which has never been conducted with survey and research on JKN patient satisfaction level.